OMEN ENTREPRENEURSHIP IN INDIA WITH SPECIAL REFERENCE TO SHE TAXI PROJECT, KERALA - ARUN.K.V AND HARIS UNNIPULAN (ZENITH International Journal of Multidisciplinary Research, 2015)
Women are generally perceived as home makers with little to do with economy or commerce. But this picture is changing. In Modern India, more and more women are taking up entrepreneurial activity especially in medium and small scale enterprises. Even as women are receiving education, they face the prospect of unemployment. In this background, self employment is regarded as a cure to generate income .The Planning commission as well as the Indian government recognizes the need for women to be part of the mainstream of economic development. Women entrepreneurship is seen as an effective strategy to solve the problems of rural and urban poverty. Traditionally, women in India have been generally found in low productive sectors such as agriculture and household activities. . The role of women entrepreneurs is especially relevant in the situation of large scale unemployment that the country faces. The modern large scale industry cannot absorb much of labour as it is capital intensive. The small scale industry plays an important role absorbing around 80% of the employment. The present study focuses on the development of women entrepreneurship in India with special reference to the She Taxi project in Kerala.